Agarose- and alginate-based biopolymers for sample preparation: excellent green extraction tools for this century - Sanagi, Mohd. Marsin (2016)
Recently, there has been considerable interest in the use of miniaturized sample preparation techniques before the chromatographic monitoring of the analytes in unknown complex compositions. The use of biopolymer-based sorbents in solid-phase microextraction techniques has achieved a good reputation. A great variety of polysaccharides can be extracted from marine plants or microorganisms. Seaweeds are the major sources of polysaccharides such as alginate, agar, agarose, as well as carrageenans. Agarose and alginate (green biopolymers) have been manipulated for different microextraction approaches. The present review is focused on the classification of biopolymer and their applications in multidisciplinary research. Besides, efforts have been made to discuss the state-of-the-art of the new microextraction techniques that utilize commercial biopolymer interfaces such as agarose in liquid-phase microextraction and solid-phase microextraction.